Response Inhibition in Preschoolers at Familial Risk for Attention Deficit Hyperactivity Disorder: A Behavioral and Electrophysiological Stop‐Signal Study. Issue 5 (28th February 2013) - Berger, Andrea; Alyagon, Uri; Hadaya, Hadas; Atzaba‐Poria, Naama; Auerbach, Judith G.
Abstract : Children participating in the Ben‐Gurion Infant Development Study were assessed with a dynamic‐tracking version of the stop‐signal task at the age of 5 years. The sample consisted of 60 males. Stop‐signal reaction time (SSRT) was correlated with concurrent ratings of the child's attention deficit hyperactivity disorder (ADHD) symptoms. Paternal symptoms measured in the child's early infancy predicted the child's performance in the stop‐signal task: Paternal inattentiveness predicted SSRT, whereas hyperactivity predicted error proportion. Maternal symptoms were not correlated with the performance of the child in the task. A subsample of children, who were tested while electrophysiological brain activity was measured, showed that having higher ADHD symptomatology, especially hyperactivity, correlated with less activity in the brain areas that are usually recruited by children for successful inhibition.